TANGGAPAN AKUNTAN PUBLIK DAN IAPI TERHADAP PENERBITAN EXPOSURE DRAFT PANDUAN INDIKATOR KUALITAS AUDIT PADA KAP - WINDAYANI, RISTI; NYOMAN ALIT TRIANI, NI (Jurnal Akuntansi AKUNESA, 2017)
This study aims to determine the responses of public accountants and IAPI to the issuance of exposure draft audit quality indictor guidelines on public accountants firm. IAPI together with P2PK establish audit quality indicators in the exposure draft audit quality indicator guidance on public accountant firm with the purpose of encouraging the improvement of audit services quality and increasing public trust in the practice of the public accounting profession. This research uses the prespective form the side of public accountant as the object which will implement the regulations, and re-communicate responses to the IAPI as the Associate profession of public accountant who issued the regulation. The result of the study indicates that all informants who are public accountants provide positive responses and support the issuance of the exposure draft of the audit quality indicators guidelines and wishes to the IAPI as the publisher to immadiately formalize and officially release the draft exposure so that is no longer voluntary but binding on the entire KAP.